Characterization of chitinase‐producing Serratia and Bacillus strains isolated from insects. Issue 3 (23rd May 2014) - Han, Kook‐Il; Patnaik, Bharat Bhusan; Cho, Ah‐ra; Lim, Ho Kab; Lee, Jae Min; Jang, Young Geun; Jeong, Yun Seon; Yoo, Tae Kyeong; Lee, Gyeong Seok; Han, Man‐Deuk
Abstract Chitinases (EC 3.2.1.14) are enzymes that hydrolyze chitin by cleaving β‐1, 4 N‐glycosidic bonds. These enzymes have been used for multiple applications in biotechnology, especially for controlling insect pests and phytopathogenic fungi. In the present study, we isolated two chitinase‐producing bacteria strains from insects (strain SCH‐1 from Moechotypa diphysis and strain SCH‐2 from Sphedanolestes impressicollis). Serratia sp. SCH‐1 was a short, rod‐shaped facultative anaerobe, while Bacillus strain SCH‐2 was a rod‐shaped endospore‐forming anaerobe. Strains SCH‐1 and SCH‐2 were identified as Serratia sp. and Bacillus sp., respectively based on 16S rRNA gene sequencing. Strain SCH‐1 shared maximum homology (99.44%) with Serratia nematodiphila DZ0503SBS1 and Serratia marcescens subsp. sakuensis KRED. Strain SCH‐2 had a maximum homology of 99.24% with Bacillus thuringiensis ATCC 10792 and Bacillus toyonensis BCT‐7112. Serratia sp. SCH‐1 contained greater levels of saturated fatty acids, but the concentration of branched acids, especially iso‐C15:0, was highest in Bacillus sp. SCH‐2. Serratia sp. SCH‐1 possessed chitinase activity of 1.59 unit/mg protein after 5 days of incubation in culture medium. In contrast, Bacillus sp. SCH‐2 had a maximum activity of 0.84 unit/mg protein after 4 days of incubation. Chitinase isozymes produced by Serratia sp. SCH‐1 appeared as five bands with sizes of 20, 26, 36, 45 and 54 kDa. Bacillus sp. SCH‐2 showed a chitinase isozyme profile with three bands having sizes of 36, 45 and 50 kDa on SDS‐PAGE gels.